Microsoft encarta world atlas - Microsoft Corporation (Redmond, WA : Microsoft, 1998)
A multimedia world atlas which includes images, music and sound clips. Spectacular 3-D virtual flights, 1.2 + million place names, 5000 + comprehensive articles, 9000 +internet links.
Title from disc label
Contains Internet Explorer software
Windows system requirements:Multimedia PC with 486DX/50 MHz or higher processor ; Microsoft Windows 95 operating sytem or Windows NT workstation operating system version 4.0 or later ; 8 MB of memory (RAM) for windows 95 (16 MB recommended); 16 MB for Windows NT Workstation (24 MB recommended) ; 29 MB of available hard-disk space ; Double-speed or faster CD-ROM drive ; Super VGA, 256-colour monitor supporting 640x480 or higher resolution ; Microsoft mouse, Microsoft intellimouseTM or compatible pointing device ; sound card and speakers or headphones.
Keywords: Atlases -- Interactive multimedia; Interactive multimedia; Computer software; CD-ROMs.